Apakah Manajemen Laba di Bank Syariah Berbeda dengan Bank Konvensional? - Adela Yohana; Vanica Serly (Universitas Negeri Padang, 2020)
This research is in the form of quantitative correlation. The correlation method is a research method with the aim of describing two or more facts and also the properties of the object being studied. This study aims to determine the differences in earnings management in Islamic banks with earnings management in conventional banks registered with the Financial Services Authority from 2015-2019. The data used in this study are the annual reports of Islamic banks and conventional banks registered with the Financial Services Authority for the period 2015-2019. The data sampling method uses purposive sampling method based on certain criteria. Based on the criteria used, the researcher obtained a sample of 34 banks. Testing the hypothesis in this study using multiple regression analysis and coupled with a different test (independent sample t-test). The results showed that there is a difference between earnings management in Islamic banks and conventional banks. Earnings management in Islamic banks is lower than conventional banks. Keywords: Conventional bank, Islamic bank, Earnings management.